Centro de gastronomía y entretenimiento - Chaverri, Felipe (2015)
The Food and Entertainment Center was a practice of architectural project Design Workshop Level 7, Group 02, of the School of Architecture at the University of Costa Rica(UCR), in the second half of 2014. This project was located in the northeast downtown San José, Costa Rica.